DISTANCE CORRELATIONS DO NOT SCALE WITH SIZE CORRELATIONS OF TREE SPECIES IN A TROPICAL RAIN FOREST STAND - Hong Hai, Nguyen; Trung Hung, Le (Journal of Forestry Science and Technology, 2016)
Spatial patterns of forest trees have been long recognized as evidences of underlying biological processes within forests. We used point pattern analysis methods and process-based models to detect the demography and dynamics of trees in a primary rainforest stand. A fully mapped 1-ha plot was investigated in the tropical rain forest of Cuc Phuong National Park. Trees were stem-mapped, diameter-measured at breast height and classified into species. Spatial patterns and tree size correlations of life-history stages, intra-species and inter-species were analyzed using the pair-correlation and r-mark-correlation functions to reveal scale dependent patterns. At the community level, sapling and juvenile stages were clustered up to large scales, while pre-mature and mature trees were regular and had random distributions, respectively. The strong evidence of competitive interaction was shown by distance correlations. However, tree sizes did not correlate significantly to the same tendency with tree-tree distances. In intra-specific interactions, three of four abundant species were significantly clustered while negative correlations in tree size were clearly shown within Hydnocarpus kurzii and Saraca dives. In addition, marginal repulsions were found in distance correlations approved by size correlations when considering the inter-specific interactions with dominant species. We suggest that self-thinning was an important driver of the forest community dynamics. Clustered distributions were predominant among conspecific trees. Weak inter-specific interactions between light demanding species (S. dives) and other species can be explained by competition for light. High diversity of species could cause the equilibrated competition for limited resources as an overall competitive effect. Here, tree size (diameter at breast height) correlations and inter-tree distance correlations did not scale well, however they also indicated competitive interactions between tree individuals.